2004
DOI: 10.1016/j.ejheart.2003.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Use of NT‐proBNP in routine testing and comparison to BNP

Abstract: Objectives: B-type natriuretic peptide (BNP) is a strong diagnostic predictor of left-ventricular (LV)-dysfunction. Recently, the aminoterminal portion of pro-BNP (NT-proBNP) has been introduced, which could be even more sensitive because of its longer half-life. The aim of this study was to evaluate the new marker NT-proBNP within a large, heterogeneous population of patients with suspected cardiovascular disease at risk of cardiovascular dysfunction and to compare it with the established diagnostic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 13 publications
5
96
1
4
Order By: Relevance
“…However, the presence of atrial fibrillation may lead to a substantial increase in left atrial overload in the setting of MS that may give rise to a further increase in BNP levels. The lack of association between the left atrial pressure and plasma levels of NT-proBNP is most likely due to the rel-Vol 48 No 5 atively small number of patients with atrial fibrillation included in the present study. Taken together with previous reports on BNP and atrial fibrillation, we may speculate that continuous pressure load on the left atrium may account in part for the increased levels of NT-proBNP despite the absence of a statistically significant correlation between left atrial pressure and plasma NT-proBNP levels.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…However, the presence of atrial fibrillation may lead to a substantial increase in left atrial overload in the setting of MS that may give rise to a further increase in BNP levels. The lack of association between the left atrial pressure and plasma levels of NT-proBNP is most likely due to the rel-Vol 48 No 5 atively small number of patients with atrial fibrillation included in the present study. Taken together with previous reports on BNP and atrial fibrillation, we may speculate that continuous pressure load on the left atrium may account in part for the increased levels of NT-proBNP despite the absence of a statistically significant correlation between left atrial pressure and plasma NT-proBNP levels.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, plasma NT-proBNP levels were decreased after PBMV and the percentage decrease in systolic pulmonary artery pressure was the only factor that associated with the percentage decrease in NT-proBNP levels. These find-Vol 48 No 5 ings imply that measurement of plasma NT-proBNP after PBMV may be useful for evaluating changes in pulmonary artery pressure. Larger prospective studies are needed to confirm our findings and identify the definite secretion site of NTproBNP in the setting of MS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23] Studies in adults have shown that NT-proBNP is a more sensitive and more specific marker for ventricular dysfunction than the biologically active BNP. 24,25 Previous studies in healthy full-term infants showed that the plasma BNP level rapidly rises after birth, reaching its peak at day 2-3 of life 26-28 and a high plasma BNP level correlates with HsPDA. A decline of BNP level is noted after PDA is closed by indomethacin.…”
mentioning
confidence: 99%